2013
DOI: 10.1002/2013ja019153
|View full text |Cite
|
Sign up to set email alerts
|

First storm‐time plasma velocity estimates from high‐resolution ionospheric data assimilation

Abstract: This paper uses data assimilation to estimate ionospheric state during storm time at subdegree resolution. We use Ionospheric Data Assimilation Four‐Dimensional (IDA4D) to resolve the three‐dimensional time‐varying electron density gradients of the storm‐enhanced density poleward plume. By Estimating Model Parameters from Ionospheric Reverse Engineering (EMPIRE), we infer the three‐dimensional plasma velocity from the densities. EMPIRE estimates of ExB drift are made by correcting the Weimer 2000 electric pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 27 publications
0
21
0
Order By: Relevance
“…Another assimilation model developed by Datta‐Barua et al . [] was used to estimate the storm time E × B drift, one of the important forcings from the electron density observations. Chartier et al .…”
Section: Introductionmentioning
confidence: 99%
“…Another assimilation model developed by Datta‐Barua et al . [] was used to estimate the storm time E × B drift, one of the important forcings from the electron density observations. Chartier et al .…”
Section: Introductionmentioning
confidence: 99%
“…The EMPIRE algorithm as previously formulated without Kalman filtering was detailed in Appendix of Datta‐Barua et al []. This study builds on the previous work by reconfiguring EMPIRE to correct for horizontal neutral winds (in contrast to the magnetic field‐aligned wind component only), ingest neutral wind data from an FPI, and implement a Kalman filtering scheme.…”
Section: Construction Of the State Vector Without Neutral Wind Ingestionmentioning
confidence: 99%
“…Details on how these are used for this study can be found below and in section 3.1. Equations are identical to previous versions of EMPIRE [ Datta‐Barua et al , , , ].…”
Section: Construction Of the State Vector Without Neutral Wind Ingestionmentioning
confidence: 99%
See 2 more Smart Citations